Natural and man-made cellulose fibre-reinforced poly(lactic acid)(PLA)composites: An overview about mechanical characteristics and application areas - Graupner, N.; Herrmann, A.S.; Müssig, J.
The paper describes the production and the mechanical characteristics of composites made completely of renewable raw materials. Composites of different kinds of natural fibres like cotton, hemp, kenaf and man-made cellulose fibres (Lyocell)with various characteristics were processed with a fibre mass proportion of 40
Keywords: FIBRES; A. THERMOPLASTIC RESIN; B. MECHANICAL PROPERTIES; E. MOULDING COMPOUNDS; POLY(LACTIC ACID)(PLA)